METHODOLOGICAL FOUNDATIONS OF THE DEVELOPMENT OF SPEECH OF PRIMARY SCHOOL STUDENTS AND ITS IMPORTANCE IN THE EDUCATIONAL PROCESS - Turanazarova Nilufar (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
This article is aimed at highlighting the methodological aspects of the development of speech of Primary School students. In the speech activity of students, attention is paid to the formation of such important aspects as pronunciation, grammar and speech enrichment. It is also emphasized that it is important for students to form a culture of communication, adherence to literary language norms, a culture of speech based on the rules of etiquette.